2022
DOI: 10.3892/etm.2022.11407
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E‑coated dialyzer alleviates erythrocyte deformability dysfunction in patients with end‑stage renal disease undergoing hemodialysis

Abstract: Patients with end-stage renal disease (ESRD) are characterized by augmented oxidative stress (OS) due to the imbalance between the generation of increased concentrations of oxidative molecules and decreased antioxidant capacity. Vitamin E-coated dialyzer membranes (VEMs) have previously been reported to alleviate the imbalance of redox metabolism in patients with ESRD undergoing hemodialysis (HD); however, their effect on the deformability of red blood cells (RBCs) remains unknown. In the present study, 48 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In a recent dose-response study of Zhang et al (2022) in patients with end-stage renal disease, it was found that higher levels of serum vitamin E resulted in a higher anti-oxidant status and a consequently lower oxidative stress as measured by the total reactive oxygen species.…”
Section: Effects Of Vitamin E On Renal Oxidative Stressmentioning
confidence: 99%
“…In a recent dose-response study of Zhang et al (2022) in patients with end-stage renal disease, it was found that higher levels of serum vitamin E resulted in a higher anti-oxidant status and a consequently lower oxidative stress as measured by the total reactive oxygen species.…”
Section: Effects Of Vitamin E On Renal Oxidative Stressmentioning
confidence: 99%
“…As discussed above, vitamin E-coated membranes can significantly scavenge ROS and improve total antioxidant status as well as red blood cell antioxidant status in dialysis patients [18]. Growing evidence also shows that vitamin E-coated membranes can prolong erythrocyte lifespan, reduce erythrocyte fragility, and alleviate erythrocyte deformability dysfunction during hemodialysis [19, 20]. Accordingly, several clinical studies have been conducted to investigate whether vitamin E-coated membranes could improve anemia in patients receiving long-term hemodialysis.…”
Section: Current State-of-the-art On the Use Of Commercial Vitamin E-...mentioning
confidence: 99%
“…Twenty-four experimental studies involving 512 patients receiving dialysis were selected for the meta-analysis, including 16 non-RCTs [14][15][16][17][18][19][21][22][23][24][25]27,28,30,32,35] and 8 RCTs. [20,26,29,31,33,34,36,37] Fourteen studies were related to the treatment results of patients receiving HD and VEMs. [15,[17][18][19][20]22,24,25,27,30,32,33,35,37] The study population included participants from Europe, [15,17,18,20,24,27,30,32,33,35] Asia [25,37] and Oceania.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…[20,26,29,31,33,34,36,37] Fourteen studies were related to the treatment results of patients receiving HD and VEMs. [15,[17][18][19][20]22,24,25,27,30,32,33,35,37] The study population included participants from Europe, [15,17,18,20,24,27,30,32,33,35] Asia [25,37] and Oceania. [19,22] The intervention duration varied from 3 weeks to 6 months.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%